PEMANFAATAN BUAH MANGROVE PEDADA (Sonneratia sp) SEBAGAI CAMPURAN PAKAN UNTUK MENINGKATKAN PERTUMBUHAN IKAN MAS - Gusman, Ery; Cahyadi, Jimmy (Jurnal Harpodon Borneo, 2015)
Feed was the most valueable input cost in aquaculture process (fish and shrimp) and very influenced toward cultivan growth. Therefore artificial feed from manufacture always facing to the cost problem in providing raw material that always rise. The purposes of this research is to find out the advanteges from mangrove fruits as alternative raw material for artificial feeding and also to searching the ability of mangrove fruits in artificial feed to increasing the growth of carps fish. This research was done from April 2015 until May 2015 at aquacultute technology laboratory, Faculty Fishieries and Marine, University of Borneo Tarakan, North Borneo. The fruits of mangrove that was used is Pedada (Sonneratia sp.). The design of this research is randomized completely design with 4 treatment that are : A (Control, manufacture artificial feed), B (Pedada 30%), C (Pedada 40%), and D (Pedada 50%). The high value of Specific Growth Rate is treatment C (Pedada powder with protein concentration 40%) 1.66%, followed by treatment D (Pedada powder with protein concentration 50%) 1.44%, treatment A (Control) 1.14%, and treatment B (Pedada Powder with protein concentration 30%) 0.84%. The high value of absolute growth is in treatment C (Pedada powder with protein concentration 40%) followed by treatment D (Pedada powder with protein concentration 50%), treatment A (Control,manufacture artificial feed), and treatment B (Pedada powder with protein concentration 30%). The value of Feed Convertion Rate is about 1.05-1.42, more high than manufacture artificial feed (0.99). the high value of Survival Rate reached by treatment C (80%), followed by treatment B (73.33%), treatment D (70%) and treatment A (53.33%). Keywords : mangrove fruit, Sonneratia, artificial feed, fish, Common carp